Proposing a new framework for personal brand positioning - Maysam Shafiee; Shabnam Gheidi; Maryam Sarikhani Khorrami; Hooshang Asadollah (European Research on Management and Business Economics (ERMBE), 2020)
Personal branding is one of the newest topics in branding. It means that each person can have a stable personal brand by considering his/her given goals and using proper strategies. In this paper, the authors have tried to present a framework for personal brand positioning. To achieve this aim, a desk research was performed using meta/synthesis and experts' poll to extract effective factors and indexes including strategy-based, capability-based, differentiation-based, audience-based, and performance-based dimensions. To measure and evaluate the indexes of framework dimension, a questionnaire was given to and completed by 200 experts in branding field. Questionnaire reliability was measured to be 0.854 by Cronbach's alpha. To evaluate the validation of the questionnaire, content validation method was used. The data was analyzed using structural equations modeling and LISREL software to represent the final framework. The results showed that the framework is well fitted for determining personal brand positioning and the pertaining indexes.
Keywords: M37; M31; 650; Personal branding; Personal brand; Brand positioning; Personal brand positioning